1989
DOI: 10.5980/jpnjurol1989.80.1816
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bacterial Defense Mechanism of the Urinary Bladder

Abstract: Bacterial adherence to mucosa is thought to be an initial and important stage to cause urinary tract infection. Among some mechanisms of bacterial adherence, the role of fimbriae and its receptor is worthy of notice. In particular, type 1 fimbriae, for which mannose is assumed as a receptor, is reported as the most common type and called "common fimbriae". Therefore if a certain amount of mannose is present in urine, it will cover the fimbriae of bacteria and competitively block the bacterial adherence to blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Pre-formed clumps could only be dissolved at the highest mannose concentration (1 M) (A) Table illustrating the sustained presence of Umod-type 1 piliated E. coli clumps when incubated at different D-mannose (Man) concentrations. The normal physiological range of Man concentration in the urine (60) is highlighted in yellow. + denotes the presence of clumps observed at t = 0 for all conditions.…”
Section: Fig S15 D-mannose Does Not Efficiently Disassemble Pre-forme...mentioning
confidence: 99%
“…Pre-formed clumps could only be dissolved at the highest mannose concentration (1 M) (A) Table illustrating the sustained presence of Umod-type 1 piliated E. coli clumps when incubated at different D-mannose (Man) concentrations. The normal physiological range of Man concentration in the urine (60) is highlighted in yellow. + denotes the presence of clumps observed at t = 0 for all conditions.…”
Section: Fig S15 D-mannose Does Not Efficiently Disassemble Pre-forme...mentioning
confidence: 99%
“…[1] Mannose are generally found in a number of fruits (including cranberries), [2] and dextro mannose (D-mannose) is thought to keep bacteria from remaining on the walls of the urinary tract, which is why it is used to prevent and treat urinary tract infections. [3] Mannose and glucose are different from each other since they are epimers at the C2 position but, surprisingly, many of their physical behaviours are different. [4] In addition, there are two possible stereoisomers at the C1 position, two possible orientations (axial/equatorial) of the hydroxyl group, thus resulting in two anomers, namely, α-D-mannose and β-D-mannose.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, good affinity of mannose and mannosides to E.coli type 1 pilus structures has been shown by several in vitro experiments [ 57 60 ]. Furthermore, based on an animal trial even at concentrations as low as 20 μg/ml, D-mannose can efficiently block uropathogenic E. coli adhesion to the urinary tract, subsequently lowering the risk for UTI [ 61 ]. Several clinical trials have assessed the potential of D-mannose supplementation to improve either acute clinical and symptomatic outcome of UTI or/and shorten the time-to-relapse in rUTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Bouckaert et al [ 57 ] demonstrated that the affinity of mannose to FimH is very high, especially compared to other monosaccharides (fructose 15-fold less, glucose 4000-fold less). Animal trials have shown that free D-mannose in urine, even in low concentrations (< 20 μg/ml) can inhibit bacterial adherence mediated by type 1 pili to urinary tract mucosa of pigs [ 61 ]. A rat study by Michaels et al , [ 62 ] demonstrated that beneficial effects on bacteriuria can be reached already after one day of saccharide injection (D-mannose or D-glucose), the efficacy being dependent on both the injected dose and the amount of E. coli .…”
Section: D-mannose and Uropathogenic E Colimentioning
confidence: 99%